Emergency medical services employing intra-arrest transport less frequently for out-of-hospital cardiac arrest have higher survival and favorable neurological outcomes. (November 2021) - Grunau, Brian; Kawano, Takahisa; Rea, Thomas D.; Okubo, Masashi; Scheuermeyer, Frank X.; Reynolds, Joshua C.; Heidet, Matthieu; Drennan, Ian R.; Cheskes, Sheldon; Fordyce, Christopher B.; Twaites, Brian; Christenson, Jim
Abstract: Background: There is substantial regional variation in out-of-hospital cardiac arrest (OHCA) survival. We investigated whether regional emergency medical services (EMS) intra-arrest transport (IAT) practices are associated with patient outcomes. Methods: We performed a secondary analysis of a multi-center North American clinical trial dataset, which enrolled EMS-treated adult OHCA cases from 49 regional population-based clusters. The exposure of interest was regional-level intra-arrest transport (IAT), calculated as the proportion of cases in each cluster transported to hospital prior to return of spontaneous circulation, examined as quartiles and as a continuous variable. Multilevel mixed-effects logistic regression modeling estimated the association between regional IAT with survival to hospital discharge and favorable neurologic status (modified Rankin Scale ≤ 3) at hospital discharge. Results: Of 26, 148 subjects (median age 68 years; 36% female; 23% shockable initial rhythm) 2424 (9.3%), survived to hospital discharge and 1993 (7.6%) had favourable neurological outcomes. Across regional clusters, IAT ranged from 0.84% to 75% (quartiles <6.2%, 6.2–19.6%, 19.6–30.4%, and ≥30.4%). For each quartile, 13.3%, 7.9%, 7.4%, and 4.8% survived, and 10.4%, 7.8%, 7.4%, and 4.8% had favourable neurological status. Regional IAT (per 10% change) was associated with decreased probability of survival (AOR 0.86, 95% CI 0.82–0.91) and favorable neurological outcome (AOR 0.80, 95% CI 0.76–0.85). Conclusion: Treatment within a region that utilizes IAT less frequently was associated with improved clinical outcomes at hospital discharge. These findings may account for some of the known regional variation in OHCA outcomes.